(untitled) (Al-Academy, 2025)
The graphic achievement is considered a wide space in which symbols, indicative signs, and suggestions that direct us towards a specific idea are gathered, thanks to the development witnessed by the designer today. The graphic achievement is characterized by a group of calls at the level of form and expression, which led to semantic, functional, and aesthetic transformations. This communicative discourse breaks down Grammar and aesthetic form, and reaches the stage of westernization, making the graphic achievement achieve an impact on a global level